2021
DOI: 10.1016/j.apsb.2021.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine ester derivative inhibits glioblastoma by inducing mitochondria-dependent apoptosis and autophagy by PI3K/AKT/mTOR and AMPK/mTOR pathway

Abstract: Glioblastoma multiforme (GBM) in the central nervous system is the most lethal advanced glioma and currently there is no effective treatment for it. Studies of sinomenine, an alkaloid from the Chinese medicinal plant, Sinomenium acutum , showed that it had inhibitory effects on several kinds of cancer. Here, we synthesized a sinomenine derivative, sino-wcj-33 (SW33), tested it for antitumor activity on GBM and explored the underlying mechanism. SW33 significantly inhibited proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 52 publications
(56 reference statements)
0
50
0
Order By: Relevance
“…It has been reported that SN can stimulate the differentiation of peripheral blood mononuclear cells into imDCs and further inhibit the maturation of imDCs[ 13 ]. SN can reduce the expression of CCR5 and CCR7 on DCs, inhibit secretion of chemokines CXCL9 and CXCL10, block expression of TLR2 and TLR4 in peripheral blood DCs, stimulate differentiation of monocytes into imDCs, and inhibit their further maturation[ 33 ]. Due to the mild drug properties of SN, short half-life, lack of toxicity below a certain dose, and lack of mutagenicity, the compound was used to induce bone marrow stem cells to differentiate into imDCs (SN-BM-imDCs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that SN can stimulate the differentiation of peripheral blood mononuclear cells into imDCs and further inhibit the maturation of imDCs[ 13 ]. SN can reduce the expression of CCR5 and CCR7 on DCs, inhibit secretion of chemokines CXCL9 and CXCL10, block expression of TLR2 and TLR4 in peripheral blood DCs, stimulate differentiation of monocytes into imDCs, and inhibit their further maturation[ 33 ]. Due to the mild drug properties of SN, short half-life, lack of toxicity below a certain dose, and lack of mutagenicity, the compound was used to induce bone marrow stem cells to differentiate into imDCs (SN-BM-imDCs).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that imDCs phagocytose apoptotic DCs, transform into tolerance DCs, and then induce naïve T cells to differentiate into FoxP3 + Treg cells[ 34 ]. Some studies have also confirmed that SN could inhibit glioblastoma by inducing mitochondria-dependent apoptosis and autophagy by PI3K/AKT/mTOR and AMPK/mTOR pathway[ 33 , 34 ]. However, there is no report on SN-induced apoptosis of DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, caspase-3-induced cleavage of autophagy-related proteins also induces apoptosis [ 58 ]. Autophagy has also been shown to be mutually associated and regulated by the cell cycle [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sinomenine is the main active ingredient isolated from the Chinese medicinal Caulis Sinomenii for the treatment of rheumatic diseases, and has the biological effects of anti-inflammation, anti-oxidation, inhibition of apoptosis, immunosuppression, etc ( 56 58 ). Clinical studies have shown that ( 59 , 60 ) sinomenine has a significant effect on the treatment of RA.…”
Section: Alkaloidmentioning
confidence: 99%